Pengaruh Promosi, Kualitas Produk, Dan Brand Image Terhadap Minat Beli Konsumen Di Koperasi Sinau Andandai Ekonomi (SAE) Pujon - Muhammad Fatchur Rohman; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study was conducted to determine the effect of promotion, product quality, and brand image on consumer buying interest in the Koperasi SAE Pujon. This research uses explanatory research and quantitative approach. Maholtra's theory was used to take samples, namely the number of items x 5 so that a total sample of 80 people was found. To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test, classical assumption test. The study used multiple linear analysis with the help of SPSS 25.0 The results of this study are the variables Promotion, Product Quality, and Brand Image affect consumer buying interest simultaneously, partially Promotion, Product Quality, and Brand Image variables affect consumer buying interest in the Koperasi SAE Pujon. Keywords: Promotion, Product Quality, Brand Image